Perbandingan Penggunaan Dolomit (CaMg) Dan Karbonat (Ca(Co3) Dalam Mempercepat Pertumbuhan Miselium Dan Pin head Jamur Tiram (Pleourotus ostreatus) - Stevany Ulukyanan; Irba Djaja; joana mendes; rosmala widijastuti (Musamus Journal of Agrotechnology Research, 2022)
ABSTRACT The Comparison of the use of Dolomite (CaMg) and Building Lime (CaCo3) in Enhancing Mycelium Growth of Oyster Mushroom (Pleurotus ostreatus)” supervised by Ling Irba Djaja, and Johana Anike Mendes. This study aims to determine the difference between the addition of dolomite and carbonate on the growth of the mycelium of oyster mushrooms and pinhead, to find out the best treatment between the addition of dolomite and carbonate for the growth of mycelium of oyster mushrooms and pinhead. This research was carried out at the House of Brawijaya street, Mandala Village, Merauke Regency, from May to July 2021. This study was compiled using a Completely Randomized Design (CRD) consisting of 2 treatments and repeated 3 times. The results of this study indicate that the administration of dolomite and carbonate has a significant effect on the growth rate of mycelium and has no significant effect on the growth of pinhead. The mycelium growth rate was in treatments D1 and D3 with an average of 27.3 days after planting, while the best pin head growth was in treatment B3 with an average of 24 days after planting. So the results of this study indicate that the administration of dolomite and carbonate has a good effect on the growth of mycelium and pin head of oyster mushrooms. Keywords: Dolomite, carbonate, mycelium, pinhead